Media Literacy as a Strategy to Counter Political Hoaxes in the Digital Public Space - R. Yogie Prawira (Global Writing Academica Researching and Publishing, 2025)
The spread of political hoaxes in the digital public sphere has increased sharply in the lead-up to elections and threatens democratic stability. Downstream regulatory-punitive and technical approaches are deemed insufficient without critical awareness among social media users. This study aims to analyze the effectiveness of media literacy as a primary upstream strategy in countering the spread of political hoaxes in the digital public sphere. Using a library research approach, data was collected through a comprehensive search of scientific documents, regulations, and official reports related to political disinformation. The results show that critical media literacy has successfully shifted the role of netizens from passive consumers to independent gatekeepers. Critical thinking skills, mastery of lateral verification methodologies, and awareness of platform algorithm architecture have proven effective in reducing confirmation bias and stopping the spread of false information in echo chambers. In conclusion, media literacy is an essential long-term preventative strategy for building cybercultural immunity within society. A multi-sectoral collaboration model between the government, educational institutions, and digital platforms is needed to create a healthy, rational, and dignified digital ecosystem.